Peran Vitamin D dalam Aktivitas Penyakit Lupus Eritematosus Sistemik (LES) - Sukamto Koesnoe (PT Dexa Medica, 2022)
Systemic lupus erythematosus (SLE) is a systemic autoimmune disease that leads to various immune system dysregulation. SLE has complex pathophysiology involving interaction between factors that will produce abnormal immune response. This abnormal immune response results in inflammatory reactions throughout various organs, and this chronic process will lead to tissue and organ damage. Vitamin D has been studied for its’ role as an immunomodulator, therefore it is potential to be part of SLE management.The potential benefits of vitamin D supplementation to improve clinical conditions of SLE patients has been investigated. Some studies showed that there were positive effects after supplementation with vitamin D in SLE patients. This can be explained considering vitamin D deficiency is associated with disease activity and frequency of exacerbations in SLE. Vitamin D’s active form, calcitriol, was found to have an important role in the pathogenesis of SLE. Study found that vitamin D supplementation could help to reduce disease activity and improve clinical condition in SLE patients.